Macroeconomic policy - Marin, Alan, 1941- (Routledge, 1992)
Examines the fierce controversy between Keynesian and monetarist schools over macroeconomic policy and offers clear alternatives which emphasize the interconnectedness of policy aims in relation to current levels of inflation and unemployment.